Isolasi dan identifikasi Staphylococcus Epidermidis pada susu sapi PFH penderita mastitis subklinis di Wukirsari, Cangkringan, Sleman, DIY (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
Mastitis is an inflammation of the mammary gland, can be occured clinically or subclinically. One of the causes of mastitis is Staphylococcus epidermidis. This study was aimed to isolate and identify Staphylococcus epidermidis in subclinical mastitis PFH dairy cows in Wukirsari, Cangkringan, Sleman, DIY. Sixteen milk samples were tested with a Californian Mastitis Test (CMT), followed by inoculation in Brain Heart Infusion (BHI), planted on a blood agar plate plate (PAD) and Mac Conkey Agar (MCA) for 24 hours at 370C. The growing colonies were then grown on sugar sugar and nutrient agar (NA) media. Gram staining, catalase test, coagulase test and DNase test as bacteria confirmation.CMT test results showed 15 (93.75%) out of 16 positive milk samples suffered from subclinical mastitis. Results of isolation showed 1 (6.66%)of 16 positive samples infected with Staphylococcus epidermidis.The results of this study indicate that incidence of subclinical mastitis in the study area showed a high rate and is likely to be caused by inadequate management practices and milking procedures. The high incidence of subclinical mastitis is probably caused by other bacteria because only 6.66% is caused by Staphylococcus epidermidis.